ANALISIS FAKTOR-FAKTOR KEUANGAN TERHADAP RETURN SAHAM (Studi Empiris Perusahaan Terideks LQ45 Periode 2015-2019) - Safitri, Dewi Nur; Kusumawati, Eny (Prosiding University Research Colloquium, 2021)
This study aims to determine the effect of liquidity, profitability, cashflow, solvency, and market ratios on stock returns. In this study,liquidity is proxied by the current ratio, profitability is proxied by thenet profit margin, solvency is proxied by the debt to equity ratio, andthe market ratio is proxied by earnings per share. This research wasconducted on companies listed on the LQ45 index of the IndonesiaStock Exchange (IDX) for the period 2015-2019. The samplingtechnique used in this study was purposive sampling technique. Thesample used in this study were 25 companies and conducted for 5years to produce 125 data. The data analysis technique used ismultiple linear regression analysis. The results showed that thevariables of liquidity and profitability had an effect on stock returns,while the variables of cash flow, solvency, and market ratios had noeffect on stock returns.